2000
DOI: 10.1074/jbc.m001760200
|View full text |Cite
|
Sign up to set email alerts
|

Elements of the Primary Structure of Thrombomodulin Required for Efficient Thrombin-activable Fibrinolysis Inhibitor Activation

Abstract: Deletion and point mutants of soluble thrombomodulin were used to compare and contrast elements of primary structure required for the activation of thrombinactivable fibrinolysis inhibitor (TAFI) and protein C. The smallest mutant capable of efficiently promoting TAFI activation contained residues including the c-loop of epidermal growth factor-3 (EGF3) through EGF6. This mutant is 13 residues longer than the smallest mutant that functioned well with protein C; the latter consisted of residues from the interdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 29 publications
1
99
0
1
Order By: Relevance
“…9,10,56 However, it currently appears unlikely that mutations in the lectinlike domain can appreciably influence TAFI activation, as this appears to be determined predominantly by EGF-like domains 3-5 of TM. 57,58 Mutation Asp486Tyr lies in the Ser/Thr-rich domain of TM. Although this domain has an important spacer function in positioning the thrombin biding site above the cell surface, 31 the mutation does not appear to influence this role.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,56 However, it currently appears unlikely that mutations in the lectinlike domain can appreciably influence TAFI activation, as this appears to be determined predominantly by EGF-like domains 3-5 of TM. 57,58 Mutation Asp486Tyr lies in the Ser/Thr-rich domain of TM. Although this domain has an important spacer function in positioning the thrombin biding site above the cell surface, 31 the mutation does not appear to influence this role.…”
Section: Discussionmentioning
confidence: 99%
“…These authors present evidence pointing to polymorphonucleur neutrophil-derived NADPH oxidase as a probable source of the biological oxidants that cause the TM inactivation typically observed in inflamed tissues. Oxidation of Met-388 leading to lessening of TM functions has also been the subject of studies by Wood et al (181,182) and Wang et al (175), while ROS-dependent inactivation of TM has been reported in a mouse model of vascular dysfunction and thrombosis (2). Furthermore, a relatively recent article by Stites and Froude (148) proposes that the elevated oxidative stress associated with smoking and diabetes is responsible for the prothrombotic state of these conditions by virtue of increased TM Met-388 oxidation and the subsequent decrease in circulating activated protein C levels.…”
Section: Posttranslational Regulationmentioning
confidence: 99%
“…This is not sufficient for TAFI activation, however. Further elements of EGF3 are required (54,55), comprising minimally the disulfide-bonded c-loop of EGF3. A recent study by Hall et al (56), involving replacement of surface residues with alanine, identified three mutants with decreased ability to activate TAFI, but not protein C, and another three that had the opposite characteristics.…”
mentioning
confidence: 99%